Circular from GC to Secretaries of all affiliated trade unions, 2 May 1926, re: distribution of essential supplies (page 2)
1926-05-02 "Circular from GC to Secretaries of all affiliated trade unions, 2 May 1926, re: distribution of essential supplies (page 2)" [g0697002.jpg], 2 May 1926